Protein ingestion to stimulate myofibrillar protein synthesis requires greater relative protein intakes in healthy older versus younger men - Moore, Daniel R; Churchward-Venne, Tyler A; Witard, Oliver; Breen, Leigh; Burd, Nicholas A; Tipton, Kevin D; Phillips, Stuart M (The journals of gerontology. Series A, Biological sciences and medical sciences, 2015)
Adequate protein ingestion-mediated stimulation of myofibrillar protein synthesis (MPS) is required to maintain skeletal muscle mass. It is currently unknown what per meal protein intake is required to maximally stimulate the response in older men and whether it differs from that of younger men. We retrospectively analyzed data from our laboratories that measured MPS in healthy older (~71 years) and younger (~22 years) men by primed constant infusion of l-ring-[(13)C6]phenylalanine after ingestion of varying amounts (0-40 g) of high-quality dietary protein as a single bolus and normalized to body mass and, where available, lean body mass (LBM). There was no difference (p = .53) in basal MPS rates between older (0.027±0.04%/h; means ± 95% CI) and young (0.028 ± 0.03%/h) men. Biphase linear regression and breakpoint analysis revealed the slope of first line segment was lower (p < .05) in older men and that MPS reached a plateau after ingestion of 0.40 ± 0.19 and 0.24 ± 0.06 g/kg body mass (p = .055) and 0.60 ± 0.29 and 0.25 ± 0.13 g/kg lean body mass (p < .01) in older and younger men, respectively. This is the first report of the relative (to body weight) protein ingested dose response of MPS in younger and older men. Our data suggest that healthy older men are less sensitive to low protein intakes and require a greater relative protein intake, in a single meal, than young men to maximally stimulate postprandial rates of MPS. These results should be considered when developing nutritional solutions to maximize MPS for the maintenance or enhancement of muscle mass with advancing age.